NANOFLUID AS COOLANT IN AUTOMOTIVE COOLING SYSTEM–HEAT TRANSFER CHARACTERISTICS OF CAR RADIATOR USING CU-BASED NANOFLUID - Fadhilah, S.A; Rafeq, Saleman Abdul; Hairul, B.; Nur Hazwani, Mokhtar; Nona Merry, M. Mitan (2012)
Nanofluid is a potential fluid with enhanced thermal physical properties as compared to conventional fluid. The conventional fluids such as water and ethylene glycol acted as coolants in automotive cooling system could show superior properties through dispersion of nanoparticles. The nanoparticles are either metal, non-metal or carbon nanotube (CNT) is in nano-size between 1-100 nm. This study focused on heat transfer characteristics of Cu/water Nanofluid in an automotive radiator by analyzing the thermal physical properties of the coolant; thermal conductivity () and heat transfer coefficient (). The mixture of solid nanoparticles and coolant showed that the thermal properties of the coolant were increasing with copper (Cu) nanoparticle volume fraction. By adding 10 % of Nanoparticle suspension, the heat transfer coefficient of the nanofluid was increased up to 26000 W.m-2K-1 with 92 % of percentage enhancement. Consequently, it also enhanced the heat transfer rate in the cooling system. The results showed good indicator for automotive industry to design an eco-car that sustain the energy and minimizing the environmental impact.